Extraocular muscle fixation to porous polyethylene orbital implants using 2-octyl-cyanoacrylate - Ferraz, Lucieni Cristina Barbarini [UNESP]; Schellini, Silvana A. [UNESP]; Wludarski, Sheila L.; Padovani, Carlos R. [UNESP]; Selva, Dinesh; Mueller, Sergio [UNESP] (Wichtig Editore, 2009)
Purpose. To evaluate the efficacy of bioadhesive in attaching the extraocular muscles to porous polyethylene spheres in rabbit enucleated cavities. Methods. A prospective, experimental study was performed. Eight adult New Zealand white rabbits underwent right enucleation with insertion of an unwrapped 12 mm porous polyethylene sphere. The superior and inferior rectus muscles were attached to the implant with 2-octyl cyanoacrylate placed to the underside of the muscles and application of pressure for 5 seconds. Ninety days after surgery, the orbits were exenterated and four animals underwent histologic evaluation and the other four animals tensile strength testing of the muscle-sphere attachment. Results. There were no exposures or infections of the implants and the muscles remained attached in all cases. Histologic examination showed fibrous tissue reaction at the muscle-sphere attachment with minimal inflammation of the surrounding tissues; a pseudocapsule formation around the spheres and full vascularization of the implant was also observed. There was no evidence of residual glue on histologic examination. Tensile strength testing showed that rupture force was similar between bonded muscle and the porous polyethylene sphere. Conclusions. The 2-octyl-cyanoacrylate did not cause deleterious effects in orbital tissues and provided strong adhesion between muscles and spheres. Bioadhesive may be an option for attaching the extraocular muscles to orbital implants in anophthalmic cavity reconstruction. © Wichtig Editore, 2009.
Keywords: 2-Octyl cyanoacrylate; Histology; Porous polyethylene sphere; Tensile strength testing